Green Hydrogen Production and Public Health Expenditure in Hydrogen-Exporting Countries - Raouf, Engy (International Journal of Energy Economics and Policy, 2023)
Energy resources play a significant role as a production input in many economic sectors, such as production of goods and transportation. Moreover, increased energy usage may result in increased air pollution, resulting in negative societal health effects. This paper aims to examine how the production of green hydrogen energy, as proxied by low-carbon energy production, and per capita public health spending are related. This study employs various techniques that are specific to panel data, such as panel cointegration tests, second-generation stationarity tests, and panel long-run estimates, The research has been conducted on a sample of 67 hydrogen exporting nations during the period from 2000 to 2021. The study revealed that hydrogen energy production causes a rise in per capita public health spending. Policymakers should encourage the usage and production of hydrogen energy to decrease the negative consequences of using energy that emits CO2. Reduction of carbon dioxide emissions helps nations to increase the proportion of government spending on public health per person. Furthermore, in hydrogen-exporting countries, an increase in the production of hydrogen leads to accumulate more funds from exporting hydrogen that will be used to increase spending on public health.